Exogenous Brassinolide Alleviates Salt Stress in Malus hupehensis Rehd. by Regulating the Transcription of NHX-Type Na+(K+)/H+ Antiporters - Su, Qiufang; Zheng, Xiaodong; Tian, Yike; Wang, Caihong (Frontiers in Plant Science, 2020)
Brassinolide (BL) mediates various physiological processes and improves plant tolerance to abiotic stresses. However, the effects and mechanism of exogenous BL on the salt tolerance of apple seedlings remain unclear. Herein, we investigated the role of BL in the salt stress response of Malus hupehensis Rehd., a widely grown apple rootstock. Salt-stressed apple seedlings showed significant decline in chlorophyll content and photosynthetic rate, and the application of 0.2 mg/L exogenous BL alleviated salt stress and maintained photosynthetic capacity. Exogenous BL application can strengthen the activities of superoxide dismutase and catalase and thereby eliminates ROS production induced by salt stress and promote the accumulation of proline and soluble sugar, thus maintaining osmotic balance. Furthermore, exogenous BL application decreased Na+ accumulation and increased K+ content in shoots and roots under salt stress by regulating the expression levels of Na+(K+)/H+ antiporter genes (MhNHXs). MhBZR1 and MhBZR2, which are the key transcription factors in the BR signal transduction pathway, can directly bind to the promoter of MhSOS1 and MhNHX4-1, respectively, and inhibit their expression. Our findings would provide a theoretical basis for analyzing the mechanism of exogenous BL application on the salt tolerance of apples.